Konflik dan Persatuan Akibat Dilema Identitas dalam Perspektif Komunikasi Organisasi - Canggi Araliya Aprianti Ode; Ichsan Muhammad Abduh; Rahmat Hidayat (Universitas Merdeka Malang, 2026)
The existence of an organization is not solely based on shared characteristics among members but on their ability to develop collective awareness of common goals, reflected in loyalty to the organization. Organizational identity strengthens when members form bonds that foster a sense of belonging, shared interests, and commitment. Communication plays a vital role in building emotional connections that reinforce these relationships. This paper explores how identity construction can promote unity while potentially generating conflict within the organization. Using a literature study, the research reviews books, journals, and scholarly articles relevant to organizational communication. Findings suggest that equality within an organization stems from shared values, whereas differences act as boundaries shaping self-identity and influencing individual self-esteem within the organizational context.